'Othering' of Refugees: An Anti-Thesis to Right Against Discrimination - Gulati, Jasmeet (UI Scholars Hub, 2024)
The process of ‘othering’ and the basis of ‘otherness’ separates marginal from the mainstream and is generally construed as discrimination amongst different social groups. The paper discusses the concept of ‘othering’ with specific reference to the rights of refugees, their plight in the country of refuge, and the attitude of national governments while dealing with the rights of refugees in compliance of international obligations. The process of characterizing refugees as ‘others’ in the host country directly affects their basic rights, which would otherwise be granted to them being refugees under international refugee law. Thus, discrimination stems from the very perspective with which the refugees are looked at by associating them with their problems instead of ameliorating their condition. However, this paper tries to look at the concept of ‘othering’ as a process of ‘enabling’ rather than denying. The ‘othering’ dilutes the status of refugees when used in a negative sense, leading to discrimination when they are denied rights in the host country. The paper adopts the method of descriptive analysis to study the process of ‘othering’ that can be used in a positive connotation, when ‘otherness’ is created to recognize and confer certain rights to them within the host country so that they can have more dignified presence. The cases of Syrian refugees, Rohingya refugees and the recent refugees from Ukraine are used to discuss the rights of refugees. The methodology used in this research is descriptive and analytical based on secondary resources. The research will make value addition to the literature of the conceptual analysis of ‘othering’, which can be used in a positive sense, rather than as a means of discrimination.